The petroleum industry of the People's Republic of China - Ling, H. C. (Stanford, Calif. : Hoover Institution Press, 1975)
The book presents the economic development and the use of energy resources in communist China. At that time petroleum made up only an insignificant part of China's energy supplies.
Includes index.
Includes bibliographical references: p. 243-255.
occ 16/01/2019
Loans
Keywords: Petroleum industry and trade; People's Republic of China